Genetic mechanisms of hemispheric functional connectivity in diabetic retinopathy: a joint neuroimaging and transcriptomic study - Huang, Xin; He, Yu-Xuan; Wan, Song (Frontiers in Cell and Developmental Biology, 2025)
BackgroundDR represents a major cause of global vision loss; however, the genetic basis of functional homotopy,a critical neurobiological metric reflecting interhemispheric functional synchronization, remains largely unexplored. Emerging evidence suggests that DR patients exhibiting aberrant VMHC may potentially associate with distinct transcriptional profiles. These findings could provide novel mechanistic insights into the neuropathological substrates underlying DR-related visual and cognitive dysfunction.MethodsResting-state fMRI data from 46 DR patients and 43 HCs were analyzed to compute VMHC for assessing interhemispheric functional connectivity. Spatial transcriptomic-neuroimaging associations were examined using AHBA, revealing genes significantly correlated with VMHC alterations. Subsequent analyses included functional enrichment assessment and PPI network construction.ResultsDR patients demonstrated significantly lower VMHC in bilateral LING, PoCG, and PreCG versus controls, indicating impaired interhemispheric connectivity in visual-sensorimotor networks. VMHC variations spatially correlated with 4,000 genes (2,000 positive/negative each), enriched in transcriptional regulation, mitochondrial function, synaptic activity (BP/CC/MF), and lipid metabolism/N-glycan biosynthesis (KEGG). PPI network identified hub genes (ACTB/MRPL9/MRPS6,positive; H4C6/NDUFAB1/H3C12,negative) regulating mitochondrial dynamics, cytoskeleton, and epigenetics.ConclusionThis study represents the first integration of fMRI and transcriptomics to elucidate the genetic determinants underlying VMHC disruption in DR. The findings demonstrate that impaired interhemispheric connectivity in DR involves complex interactions among genes regulating neurovascular, metabolic, and neurodegenerative pathways. These results significantly advance the understanding of neurological manifestations in DR and identify potential therapeutic targets for clinical intervention.